2013
DOI: 10.1128/mbio.00803-13
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the Hemagglutinin-Neuraminidase and Fusion Glycoproteins of Human Parainfluenza Virus Type III Regulates Viral Growth In Vivo

Abstract: Paramyxoviruses, enveloped RNA viruses that include human parainfluenza virus type 3 (HPIV3), cause the majority of childhood viral pneumonia. HPIV3 infection starts when the viral receptor-binding protein engages sialic acid receptors in the lung and the viral envelope fuses with the target cell membrane. Fusion/entry requires interaction between two viral surface glycoproteins: tetrameric hemagglutinin-neuraminidase (HN) and fusion protein (F). In this report, we define structural correlates of the HN featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
87
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(92 citation statements)
references
References 59 publications
5
87
0
Order By: Relevance
“…The HPIV3 HAEadapted strain and the CI-1 strain attain viral titers of up to 10 7 and 10 8 PFU/ml, respectively, in HAE, and greater than 10 5 PFU/g of lung tissue in cotton rats compared to those of the HPIV3 laboratory reference strain, which we previously found to peak at 10 5 PFU/ml in HAE and 10 4 PFU/g of lung tissue in cotton rats (20). Viruses collected from HAE infected with the HAE-adapted HPIV3 produced small plaques (average diameter of 0.1 mm) relative to those of the reference strain (average diameter of 0.6 mm) (19), and the CI-1 virus produced plaques similar in size to those of the HAE-adapted strain (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The HPIV3 HAEadapted strain and the CI-1 strain attain viral titers of up to 10 7 and 10 8 PFU/ml, respectively, in HAE, and greater than 10 5 PFU/g of lung tissue in cotton rats compared to those of the HPIV3 laboratory reference strain, which we previously found to peak at 10 5 PFU/ml in HAE and 10 4 PFU/g of lung tissue in cotton rats (20). Viruses collected from HAE infected with the HAE-adapted HPIV3 produced small plaques (average diameter of 0.1 mm) relative to those of the reference strain (average diameter of 0.6 mm) (19), and the CI-1 virus produced plaques similar in size to those of the HAE-adapted strain (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…None of the strains with proficient fusion activities that grow efficiently in cultured monolayer cells succeed in vivo. We observed that the HPIV3 CI-1 collected directly from a patient grew efficiently in cotton rats, producing 2 to 3 logs more virus than the laboratory reference strain at the peak of infection, similarly to the HAE-adapted strain, which we had previously found to be viable in vivo (19,20).…”
mentioning
confidence: 81%
See 3 more Smart Citations